Respons pertumbuhan bibit kopi arabika dan sifat kimia media tanam terhadap pemberian pupuk hayati dan pupuk organik - Iing Sobari; Kurnia Dewi Sasmita; Dewi Nur Rokhmah; Sakiroh Sakiroh; Handi Supriadi (Jurnal Agro, 2023)
Using soil planting media with low fertility can inhibit seedling growth. Bbiofertilizer and organic fertilizer applications in plantation nurseries aim to improve the planting media quality and stimulate seedling growth. The effectiveness of biofertilizers is thought to be influenced by the carrier formula and the planting medium characteristics. This study aimed to determine the effect of biofertilizer formulas and organic fertilizer doses on the growth of Arabica coffee seedlings and the planting media chemical properties. The experiment used a randomized block design with two factors. The first factor was biofertilizer formula types, namely without biofertilizers, 10 g polybag-1 solid biofertilizer, and 10 ml polybag-1 liquid biofertilizer. The second factor was sheep manure dosage (2%, 4%, 6%, and 8%). The results showed that the solid biofertilizers significantly increased seed vigor (height, stem diameter, and number of leaves) of coffee seedlings aged 6 MAP (months after planting). The dose of 6% manure produced the highest leaf dry weight of coffee seedlings aged 6 MAP. Increasing the dose of manure from 2% to 8% could significantly increase the pH, organic C content, P-available, CEC, exchangeable pottasium, exchangeable calsium, and exchangeable magnesium of the planting medium. The application of solid biofertilizer formula and manure can support the production of good-quality Arabica coffee seedlings.